DISTRIBUSI DAN MARGIN PEMASARAN HASIL TANGKAPAN IKAN DI BANGLIAO HASAN KELURAHAN BAGAN BARAT KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Ulfa Rizki Pradini; Eni Yulinda; Hazmi Arief (Berkala Perikanan Terubuk, 2017)
This research was conducted in February 2017 located in Bangliao Hasan, Bagan Barat Village, Bangko SubDistrict Rokan Hilir Regency. This research is aimed to know the distribution channel of sea fishery fish catching commodity which landed in Bangliao Hasan and to know the amount of marketing margin at every level of marketing institute of marine fishery commodity in Bangliao Hasan. The method used in this study is the survey method with the number of respondents as many as 50 people consisting of 1 owner of bangliao (tauke), 6 workers in bangliao, 10 fishermen, 8 agents, 2 restaurant owners, 15 retailers and 8 people of along-along where the determination of respondents conducted by census. Based on research result it is known that the institutions that play a role in the distribution of fish catch marketing in Bangliao Hasan are fishermen, tauke, agents, retailers and along-along (retailers who sells by traveling around) as well as consumers with a distribution pattern consisting of three distribution chains and the conclusion that can be taken the highest total marketing margin found in Stingray fish IDR 31.000,- and the lowest marketing margin found in Mackerel fish equal to IDR 19.000,-